Implementasi Alat Pemadam Api Ringan Berdasarkan Permenakertrans Nomor 4 Tahun 1980 Di Area Workshop Perusahaan Fabrikasi - Muhammad Rizal Nurul Kahfi; Moch. Luqman Ashari (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
This study aims to analyze the implementation of Light Fire Extinguishers (APAR) based on the Regulation of the Minister of Manpower and Transmigration No. 4 of 1980 concerning Requirements for Installation and Maintenance of Fire Extinguishers in the workshop area of fabrication companies. Researchers used descriptive research methods using qualitative analysis. The data collection technique uses the results of interviews with informants and observations using the APAR checklist in accordance with the Minister of Manpower Regulations and Transmigration No. 4 of 1980. The results of the study show that the suitability level of APAR implementation in company workshops is based on 11 elements in the checklist of the Minister of Manpower Regulation and Transmigration No. 4 of 1980, it is still 73% appropriate or in the sufficient category, so it still requires an evaluation of improvements. Keywords : Fire, Light Fire Extinguisher (APAR), Fabrication Company